Efficacy and safety of the switch of Triumeq® to generic (abacavir + lamivudine) + Tivicay®: data at 24 weeks - Olalla, Julián (BMC Pharmacol Toxicol, 2018)
BACKGROUND: Generic drugs may help to support antiretroviral treatment. We want to assess the efficacy and safety at 24 weeks of the change of coformulated (abacavir + lamivudine + dolutegravir) to (abacavir + lamivudine) coformulated as a generic pharmaceutical specialty + dolutegravir. METHODS: Between February and June 2017, switch from Triumeq® to a generic pharmaceutical specialty co-formulated tablet (abacavir + lamivudine) plus Tivicay® was made. Demographic, viroimmunological characteristics and the Charlson index were collected. Six months after switching, efficacy and safety were evaluated. RESULTS: Switch was made in 93 patients, with a mean age of 47 years, after six months there were five patients (5.4%) with viral loads between 50 and 400 copies, no patient had viral loads of greater amount. There were 2 interruptions due to toxicity (2.15%), in relation to symptoms of the central nervous system. There were no differences in the amount of years with HAART, nor in the previous months with the STR regimen based on abacavir + lamivudine + dolutegravir, nor in the Charlson index. The effective saving in 2017 derived from the change in these 93 patients was € 125.512. CONCLUSIONS: The change from a regimen of abacavir + lamivudine + dolutegravir seems to be safe and effective at 24 weeks.